CD8+HLADR+ Regulatory T Cells Change With Aging: They Increase in Number, but Lose Checkpoint Inhibitory Molecules and Suppressive Function - Lukas Yani, Stella; Keller, Michael; Melzer, Franz Leonard; Weinberger, Birgit; Pangrazzi, Luca; Sopper, Sieghart; Trieb, Klemens; Lobina, Monia; Orrù, Valeria; Fiorillo, Edoardo; Cucca, Francesco; Grubeck-Loebenstein, Beatrix (Frontiers in Immunology, 2018)
ABSTRACT CD4+ regulatory T cells have been intensively studied during aging, but little is still known about age-related changes of other regulatory T cell subsets. It was therefore the goal of the present study to analyze CD8+HLADR+ T cells in old age, a cell population reported to have suppressive activity and to be connected to specific genetic variants. We demonstrate a strong increase in the number of CD8+HLADR+ T cells with age in a cohort of female Sardinians as well as in elderly male and female persons from Austria. We also show that CD8+HLADR+ T cells lack classical activation molecules such as CD69 and CD25, but contain increased numbers of checkpoint inhibitory molecules such as CTLA-4, TIM-3, LAG-3 and PD-1, when compared with their HLADR- counterparts. They also have the capacity to inhibit the proliferation of autologous PBMCs. This suppressive activity is, however, decreased when CD8+HLADR+ T cells from elderly persons are analyzed. In accordance with this finding, CD8+HLADR+ T cells from persons of old age contain lower percentages of checkpoint inhibitory molecules than young controls. We conclude that in spite of high abundance of a CD8+ regulatory T cell subset in old age its expression of checkpoint inhibitory molecules and its suppressive function on a per cell basis are reduced. Reduction of suppressive capacity may support uncontrolled subclinical inflammatory processes referred to as “inflamm-aging”.